ANALISIS TEORI RELEVANSI DALAM ACARA ‘INI TALKSHOW’ SEBAGAI KRITIK TERHADAP PRINSIP KERJASAMA GRICE - Megawati Megawati (JIPIS, 2018)
AbstractThis article aims to analyze “Ini Talkshow” programme as a criticism toward Grice’s Cooperation Principle in communication. The data was collected from recording of Net television station, it is “Ini Talkshow” programme. Data analysis used qualitative descriptive by data transcript and was analyzed using Theory of Relevancy of Daniel Sperber dan Deirdre Wilson. The result indicates the utterances in “Ini Talkshow” program is relevant and meaningful utterances although these utterances step out of line of four maxim of communication in Grice’s Cooperation Principle. “Ini Talkshow” utterances have a contextual effect and extension of similarity cognitive environment as the result of interaction of new information and previous information between addresser and addressee. Keywords: cognitive environment, contextual effect, Grice’s cooperation principle, theory of relevancy AbstrakArtikel ini bertujuan untuk menganalisis program “Ini Talkshow” sebagai kritik terhadap prinsip kerjasama Grice dalam komunikasi. Data Dikumpulkan dari rekaman stasiun televisi Net, program yaitu Ini Talkshow. Analisis data menggunakan deskriptif kualitatif dengan transkrip data dan dianalisis menggunakan Teori Relevansi dari Daniel Sperber dan Deidre Wilson. Hasilnya mengindikasikan bahwa ujaran-ujaran dalam program Ini Talkshow adalah ujaran yang relevan dan bermakna walaupun ujaran-ujaran tersebut diluar dari teori komunikasi dari Prinsip kerjasama Grice. Ujaran-ujaran Ini Talkshow memiliki pengaruh kontekstual dan perluasan kesamaan lingkungan kognitif sebagai hasil dari interaksi informasi sebelumnya antara pengirim dan penerima.Kata kunci: lingkungan kognitif, pengaruh kontekstual, prinsip kerjasama Grice, Teori relevansi.